Clusters and series consonants of the Kaur language (phonological analysis) - Hadi, Wisman; Mulyono, Mulyono (Politeknik Negeri Bali, 2023)
The phonotactic system is one of the interesting phonological systems to explain because it is the system that regulates the existence, abilities, and inability of phoneme combinations of a language. To that end, this article describes the Kaur language phonotactic system which includes (1) the cluster phonotactic system and (2) the consonant series phonotactic system. The data in this study were sourced from six key informants who were domiciled in Kaur Regency (Bengkulu Province) with the criteria of being between 50-65 years old, native Kaur tribe, never left their native area, mastered Kaur language and culture well, and communicative. Data was collected through interviews and recording devices. Data were analyzed to determine the cluster and consonant series with the help of a speech analyzer. The results showed that in Kaur language (KL) there are 14 clusters (/pl/, /bl/, /gl/, /mp/, /mb/, /nt/, /nd/, /st/, /ɲc/, /ɲɟ/, /ɲcl/, /ŋk/, /ŋg/, /ŋgl/) and 21 series: /mp, mb, nt, nd, ns, ɲc, ɲɟ, ŋk, ŋg, ŋs, ʕb, ʕt, ʕd, ʕc, ʕk, ʕs, sk, st, ʔm, ʔ-ʕ, ʔ-mp/. In KL there is a unique consonant vowel sequence (homorgan consonant series). There are three rules if-then to explain the cluster of KL and five rules if-then to explain the series of KL consonants. KL has a unique phonotactic system so that this study contributes to the development of KL.